Respuesta :
[tex]n=3m+6 \\
n-2m=2 \\ \\
\hbox{substitute 3m+6 for n in the second equation:} \\
3m+6-2m=2 \\
m+6=2 \\
m=2-6 \\
m=-4 \\ \\
n=3m+6=3 \times (-4)+6=-12+6=-6 \\ \\
\boxed{(m,n)=(-4,-6)}[/tex]
Answer:
[tex](-4,-6)[/tex].
Step-by-step explanation:
We have been given a system of equations and we are asked to find the solution for given system of equations in the form (m,n).
[tex]n=3m+6...(1)[/tex]
[tex]n-2m=2...(2)[/tex]
We will use substitution method to solve linear equation. Upon substituting equation (10 in equation (2) we will get,
[tex]3m+6-2m=2[/tex]
Combine like terms:
[tex]m+6=2[/tex]
[tex]m+6-6=2-6[/tex]
[tex]m=-4[/tex]
Substituting [tex]m=-4[/tex] in equation (2) we will get,
[tex]n-2\times -4=2[/tex]
[tex]n+8=2[/tex]
[tex]n+8-8=2-8[/tex]
[tex]n=-6[/tex]
Therefore, the solution for our given system of equation is [tex](-4,-6)[/tex].